Triboelectrostatic charging behavior of pulse particles in a vortex flow tribocharger. (July 2022) - Yang, Jingsi; Zhang, Lifeng; Meda, Venkatesh; Nickerson, Michael
Graphical abstract: Highlights: Chargeability of pulse particles (protein isolate, starch, and flours) was focused. Tribocharging of three materials (copper, stainless steel, and PTFE) were compared. The specific charge decreased with decreasing the protein content for flour samples. The ideal candidate of the vortex tribocharging separation was metallic material. A "wave propagation" mode was proposed to explore the tribo-charging mechanism. Abstract: Triboelectrostatic separation (TES) has shown its great potential in dry fractionation of food ingredients. The principle of the TES technique is straightforward, i.e., charging particles through interactions of particle–particle and/or particle–wall of the contact material, followed by the effect of an electric field. However, optimization of TES efficiency is complex due to obscure understandings, unknowns, and inconsistencies in the charging mechanism between the tribocharger and the agro-food materials. To broaden the design and applications of the TES technique and shed some light on the charging mechanism, experiments were conducted in a vortex flow tribocharger made of three different materials (Copper, Stainless Steel, and PTFE) to investigate the chargeability of five type of selected pulses particles. A Faraday cup measurement system was applied to measure the electric charge of the particles collected at the core and wall regions of the tribocharger. The charges of the pulse particles induced by the vibratory feeder were also measured to verify the chargeability of the particles. Ideal charging material was suggested by comparing the specific charge of particles using the three vessels. A simple "wave propagation" mode based on the vortex flow dynamics has been proposed with an attempt to explore the role of particle–particle and particle–wall interactions on the triboelectrostatic charging.